Managing the non-profit organization - Drucker, Peter ([S.l.] : Routledge, 2004)
A Drucker management classic, first published in 1990, which breaks down any narrow definition of management and is aimed specifically at decision-makers and managers working in non-profit making and charitable organizations to help them apply the principles of good management to their sector. Drawing from the American experience, Drucker poignantly illustrates his discussion of management by quoting his in-depth interviews with top executives from non-profit making organizations. The issues of mission, performance, people and relationships, leadership and developing managers are eloquently discussed and Drucker provides Action Implications throughout the book which are of practical importance to the reader.
Keywords: Associations, institutions, etc.--Management; Nonprofit organizations--Management